Навчання мов у період карантину в Закарпатському угорському інституті імені Ференца Ракоці ІІ - Густі Ілона; Барань Єлизавета; Лехнер Ілона; Фабіян Марта; Baran Ielyzaveta; Ilona Lekhner; Huszti Ilona; Bárány Erzsébet; Lechner Ilona; Fábián Márta (Видавничий центр КНЛУ, 2021)
Резюме. У статті описано особливості дистанційного навчання. За допомогою анкетного опитування, проведеного серед викладачів, охарактеризовано своєрідність онлайн-навчання, виявлено труднощі, з якими стикнулися учасники освітнього процесу в рамках цієї форми навчання, описано процес пристосування до дистанційного навчання. Розглянуто зміни, які відбулися в повсякденні викладачівфілологів з професійного погляду. Розглянуто мотиваційну складову студентів у новостворених умовах, з’ясовано нові методи навчання, представлено методи оцінювання студентських робіт.

Abstract. The year of 2020 can be considered an exceptional one as the horrible COVID-19 broke out and spread all over the world. The new reality has totally altered the sphere of education. During the months-long Густі І., Барань Є., Лехнер І., Фабіян М. Навчання мов у період карантину в Закарпатському угорському інституті імені Ференца Ракоці ІІ 83 quarantine in Ukraine in spring 2020 educational institutions had to close and all primary, secondary and tertiary education had to transit from face-to-face learning to distance learning. Aims. This period was challenging for both students and teachers. Our main objectives were to better understand the undergoing processes and get valuable insights into how language teachers at a higher educational establishment managed to solve the tasks they had to face and complete the educational process successfully. Methods. We have created an online questionnaire for tutors to fill in. Our research instrument consisted of three parts: in the first one, we asked our 18 respondents about their personal data; in the second part the tutors were asked to indicate on a Likert-scale how much they agreed or disagreed with the given statements on issues directly related to distance learning, while in the third section of the questionnaire we requested our research participants to answer open-ended questions and express their views on how they managed to motivate their students to learn, or what caused significant problems for them during teaching online. Results. The empirical findings revealed that for most of the tutors distance teaching was a completely new area of experience as they had not tried doing it before the pandemic. They used a number of online applications; however, it was Google Classroom that was used by all of them on the initiative of their workplace. The factors that caused the most significant difficulties for the tutors were, among others, the assessment of student performance and knowledge. There was a lack of trust on the tutors’ part as to who the assignments were completed by. For some tutors it was frustrating not to be certain about whose work they were assessing – whether the students’ or somebody else’s. Conclusions. A crucial pedagogical implication derives from our empirical evidence, namely, that it is of utmost importance that tutors be trained how to teach online. They should be given the opportunity to develop their digital skills needed for distance or online teaching. Our other finding also confirms the implication that tutors must be provided with the chance to develop their skills as online teachers. In addition, it is advisable for tutors to develop mutual trust between them and their students.
Learning languages during the quarantine at the Ferenc Rákóczi II Transcarpathian Hungarian College of Higher Education
Редакційна колегія: http://visnyk-pedagogy.knlu.edu.ua/editorial-board
Зміст: http://visnyk-pedagogy.knlu.edu.ua/issue/view/14291
Keywords: дистанційне навчання; методи навчання; мотивація; методи оцінювання; distance learning; tertiary education; motivating students in online education; assessment of student performance in distance learning